Peran Indonesia Investment Authority (INA) Sebagai Sovereign Wealth Fund Dalam Mitigasi Risiko Ekonomi dan Jaminan Perlindungan Hukum Bagi Investor Asing - Fattaya, Zalfa (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The purpose of this study is to find out the role of the Indonesia Investment Authority (INA) as a Sovereign Wealth Fund in conducting national economic risk mitigation through the foreign investment scheme and legal protection guarantee mechanisms provided by the Indonesia Investment Authority (INA) to foreign and international investors based on national legal aspects. The authors in this study employed normative legal research methods, i.e., research that focuses on the study of prevailing positive legal norms as well as relevant legal doctrines. This method was chosen because the research is oriented towards the analysis of legislative regulations and legal concepts governing the Indonesian Investment Authority’s (INA) role in economic risk mitigation and legal protection of foreign investors. The results of the study show thatINA plays an effective role as a mitigating agent of fiscal and economic risks of structure al through co-investment model. INA succeeded in attracting long-term foreign equity capital from credible global investment institutions, which allows financing strategic projects without adding to the country’s debt (off-balance sheet financing). This directly reduces the country’s fiscal burden and debt risk (sovereign risk).INA also acts as a de-risking agent for foreign investors , reducing political, regulatory, and domestic project risks that often hinder FDI. In addition, the legal protection mechanism provided by the INA is a system of multi-layered protection that integrates national law and international standards. Ex-Ante Protection (National Law) i.e. INA provides high Legal Certainty through the sui generis status guaranteed by the Works Creation Act. This status confers legal superiority that mitigates the risk of unilateral regulation.